Normative coherence through social entrepreneurship: Fostering women's empowerment in Myanmar. (9th April 2022) - Perekrestova, Vlada
Summary: Motivation: Women's empowerment has been an integral part of the discussion on normative coherence for development, but its implementation is not very effective in Myanmar. Gender must be kept at the forefront of policy analysis in order to avoid unintended consequences for women. Purpose: The article argues that the Government of Myanmar lacks initiatives on women's economic empowerment, but that social enterprises could prove to be a more appropriate way to implement international norms in gender equality. Methods and approach: This case study uses descriptive research to verify how social entrepreneurship can contribute to women's empowerment by increasing women's participation in the labour market. The empirical part of this study is based on field research undertaken in February 2019. Findings: In Myanmar, there is still a gap between normative policies and social practices. Women's legal and actual equality cannot be realized by law and philosophy alone, but also depends on a shift in political, economic, and social actions to ensure that women can participate in the public sphere on an equal basis as men, and enjoy equal economic opportunities. The article explores the role that social enterprises are already playing as an example of how international development norms are implemented at the local level. Policy implications: The article highlights the appropriateness of social enterprises as catalysts of gender equality and as agents of normative gender coherence for development. Social enterprises take an inclusive and sustainable approach to addressing issues, making women's livelihoods central.